The ultimate thread guide : everything you need to know to choose the perfect thread for every project - Goldsmith, Becky, 1956- (C & T, 2020)
Always choose the right thread! This amazing reference guide features a handy thread use key (organized by thread manufacturer) that shows the most common uses for the wide variety of threads commonly used by quilters and sewists. This valuable information will help you determine which one is right for your project. Plus, get the inside scoop on thread types and fibers, thread weight, choosing the correct sewing machine needle, and how thread is made. *Learn about the most important features of specific threads (grouped by thread manufacturer) *On the go travel size *Try out new products and new techniques with confidence.